Human Resources Development for Competitive Innovation in Sharia Banks: A Case Study of BSI KCP Kopo - Nurrachmi, Intan; Refanisa Zaeni, Mutiara; Ibadurrahman, Zayd; Nazwa Khoerunisa, Fadila; Aulia Resa, Alif (El-kahfi | Jurnal Ekonomi Islam, 2025)
Along with the rapid development of technology and the increasingly globalization of the world, the banking sector faces increasingly complex challenges. Fierce competition, changing consumer behavior, and advances in information technology are forcing banking institutions to adapt and innovate in their products and services. This analysis aims to provide an in-depth understanding of the role of human resources (HR) in encouraging innovation in the banking sector, especially in Islamic banking. This study uses a qualitative approach with a phenomenological study design to explore the experiences and perceptions of Islamic banking employees about the importance of human resource competencies in supporting more competitive service innovation. The main results of the study show that human resource competencies, especially in terms of creativity, technological expertise, and understanding of sharia principles, are key factors in driving service innovation. However, Islamic banking faces major obstacles in recruiting and retaining top talent due to stiff competition with more established conventional banks, offering more attractive compensation and benefits. This study reveals how employees' perception of limitations in human resource management has a direct impact on the dynamics of innovation in the context of value-based Islamic banking. The results of the research will enrich the literature on sharia value-based HR management with a focus on the relationship between individual competencies and service innovation in the ethics-based financial sector. The success of innovation in Islamic banking is highly dependent on the quality and strategy of human resource management, which must proactively address external challenges by prioritizing value-based competency development and innovation sustainability.